Development of a technology for interactive design of garments using add-ons of a virtual mannequin - Slavinska, Alla; Zakharkevich, Oksana; Kuleshova, Svetlana; Syrotenko, Oksana (Eastern-European Journal of Enterprise Technologies, 2018)
The problem of development of the technology of interactive garment designing by engineering methods was studied, which makes it possible to use the passive mode for automated preparation of design documentation. The theoretical background for modular approaches to formalization of the structural design of clothing is the stated principles of coordination of the actions in the algorithms of transformation of the sets of a research object. The technology of construction of a geometric model of an object is represented by three kinds of information models: digital, meshed, and surface. The analytical and experimental research resulted in substantiation of the algorithm of project situations of the transformation of the surface of the original object in the form of an electronic mannequin, into the garment design. The original database for construction and modification of the frame 3D mannequin models was theoretically substantiated with a view to ensuring the reliability of their visualization. We studied the mechanism of interactive modification of surface shells of clothing in the cycle of its silhouette deformation and of the construction of flat sweeps of clothes, adapted to the vectors of modifying the mannequin surface sections in order to receive the garment designs identical to the original of the morphological structure of the consumer’s body. 4 scenarios of design situations of the regarmention and transformation of the 3D-model of the silhouette surface of a mannequin and of the garment by the optimal route were proposed to improve the speed and the quality of processes of computer-aided design of clothing parts for the figures of typical and atypical physique. The image construction apparatus of the digital model of a three-dimensional object takes into consideration the topology of the geometrical structure of a shape and the morphological field of synergies of the elements in the processes of transition from 3D to 2D designing. The scenario of the adaptation of silhouette 3D images of a garment to the modified 2D design documents grounded on database verification was proposed. Assessment of the effectiveness of the garment design technology was made by the number of iterations of project operations in design procedures with the quality level check